Review Of The Implementation Of Immigration Operation Of Foreigners Free Visa Holder Who Travel Domestically In Class I Immigration Office Tpi Mataram Relation To Legal Compliance - Adelia Rabilatun; Maidah Purwanti (Polteknik Imigrasi, 2022)
Foreigners who use free visa facility can freely travel domestically to other provinces in Indonesian. That condition affects the implementation of immigration operation which further has implications for legal compliance. This research aims to explain the implementation of immigration operation for foreigners using free visa facility who travel domestically in the area of Immigration Office Mataram. Moreover, the relation between the legal compliance and the implementation of immigration operation for foreigners who travel domestically to minimize immigration violations. This research uses a socio- legal research method that has similarities to empirical method. The results are the implementation of immigration operation for foreigners who travel domestically conducted in administrative or field (routine activities and joint operations) by Immigration Office Mataram. The relation between the legal compliance and the implementation of immigration operation is marked with the issues and factors that implicate forigners’s self-awareness who using free visa facility which create non- compliance or immigration violations. Furthermore, the compliance of forigners who using free Visa facility is connected to the compliance indicators and made in the scheme of compliance by emphasizing three elements. They are compliance of stakesholders, Registration of foreigners traveling domestically, and mapping the immigration operation areas.